2004
DOI: 10.1001/archpsyc.61.8.795
|View full text |Cite
|
Sign up to set email alerts
|

Ventromedial Prefrontal Cortex and Amygdala Dysfunction During an AngerInduction Positron Emission Tomography Study in Patients With Major DepressiveDisorder With Anger Attacks

Abstract: These results suggest a pathophysiology of MDD + A that is distinct from that of MDD - A and that may be responsible for the unique clinical presentation of patients with MDD + A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(91 citation statements)
references
References 129 publications
7
82
0
2
Order By: Relevance
“…32 Morphological and functional abnormalities within the amygdala in individuals with MDD have also been consistently demonstrated. 13,33,34 As it is possible that the decreased functional connectivity of rPFCamygdala circuitry detected in our MDD group may relate to both executive and emotional dysfunction, future neuroimaging studies using tasks that investigate these functions would be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…32 Morphological and functional abnormalities within the amygdala in individuals with MDD have also been consistently demonstrated. 13,33,34 As it is possible that the decreased functional connectivity of rPFCamygdala circuitry detected in our MDD group may relate to both executive and emotional dysfunction, future neuroimaging studies using tasks that investigate these functions would be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have demonstrated negative correlations between amygdala and medial OFC (Hariri et al, 2000(Hariri et al, , 2003. Previous fMRI studies showing negative correlations between amygdala and OFC have employed event-related designs showing acute reactions to aversive stimuli (Dougherty et al, 2004;Shin et al, 2005). Our study, in contrast, employs 18 FDG-PET, which reflects an average of activity of a 30-min epoch.…”
Section: Implications Of Group Differences In Fronto-amygdala Correlamentioning
confidence: 90%
“…Note also that the aggression seen in psychopathy [a condition associated with high BAS activity (Cole and Zahn-Waxler, 1992;Gray, 1994)] is frequently goal directed, linked to the gain of monetary and sexual rewards or social status (Cornell et al, 1996). The reduced frontostriatal response with increasing BAS drive was associated with increased amygdala activity, a similar pattern to the experience of aggression (Dougherty et al, 2004). Similarly, individuals with intermittent explosive disorder show an exaggerated amygdala response and reduced vmPFC response to aggressive facial expressions relative to controls (Coccaro et al, 2007), whereas a comparable exaggerated pattern is found in participants carrying the low-expression variant of the MAO-A (monoamine oxidize A) polymorphism (Meyer-Lindenberg et al, 2006), associated with increased risk for violent behavior (Caspi et al, 2002).…”
Section: Bas Aggression and Rewardmentioning
confidence: 94%
“…The involvement of these structures has been identified by both human and comparative research (Davidson et al, 2000;Dielenberg and McGregor, 2001;Blair, 2003;Soloff et al, 2003;Izquierdo and Murray, 2004;Coccaro et al, 2007), with heightened aggression associated with decreased vmPFC activation (thought to reflect decreased control) and increased amygdala activation (reflecting increased negative affect) (Davidson et al, 2000;Dougherty et al, 2004).…”
Section: Introductionmentioning
confidence: 99%